Composition and emission factors of traffic- emitted intermediate volatility and semi-volatile hydrocarbons (C10–C36) at a street canyon and urban background sites in central London, UK. (15th June 2020) - Xu, Ruixin; Alam, Mohammed S.; Stark, Christopher; Harrison, Roy M.
Abstract: Hydrocarbons in both gas and particle phases from C10 to C36 (I/SVOCs) were analysed at sites in central London. Samples were collected from a street canyon, Marylebone Road (MR), a rooftop site (WM) above MR, and a site in the adjacent Regent's Park (RU), north of MR to evaluate the change in composition of I/SVOCs during advection from the traffic to the cleaner atmosphere of the urban background. Groups of compounds identified and quantified in gas and particle phases include C13 –C36 n-alkanes and branched alkanes, C12 –C25 monocyclic alkanes, C13 –C27 bicyclic alkanes and C10 –C24 monocyclic aromatics. The similarities found in the aliphatic and aromatic region above C12 in urban air and diesel exhaust demonstrate the impact of diesel-powered vehicles on urban air quality. Diesel exhaust is suggested to be the dominant emission source, while small differences between sites indicate the possibility of other sources which are also discussed. The ambient concentrations of I/SVOCs in the street canyon at MR were highest when the southerly winds brought the traffic emitted pollutants to the sampler. Emission factors (EFs) for all compound groups were estimated from the concentrations at the MR site. Particle-phase n-alkane EFs are broadly similar to those measured elsewhere in the world, despite differences in traffic fleet composition. A comparison between n-alkane EFs estimated from field measurements and those measured from diesel engines in the laboratory suggests a large contribution from vehicles with higher emissions than recent passenger cars to London air. Graphical abstract: The measurements of I/SVOCs in the London Campaign 2017. Image 1 Highlights: Air sampling at roadside and urban background. Analysis by two-dimensional GC and ToFMS. Hydrocarbons from C10 –C36 quantified. Both vapour and particulate forms are analysed. Road traffic emission factor estimates for n-alkanes.